ROA Banking Profitability in the Digital Era: Analysis of Financial Performance and Macroeconomic Factors in Indonesia - Kristian Chandra; Angelina Angelina; Arnolt Kristian Pakpahan; Yuana Jatu Nilawati (Annals of Management and Organization Research, 2026)
Purpose: This study examines the impact of bank-specific factors, digitalization, and macroeconomic variables on profitability in Indonesia, measured by ROA and ROE. It focuses on how internal factors like NPL, LLP, CIR, digitalization, and CSR, along with external factors such as inflation, currency risk, and economic growth, affect bank financial performance. Methodology: This study employs panel data regression with a fixed effects model using data from 41 banking companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. A total of 205 observations were analyzed using EViews 12. Model selection was conducted using Chow and Hausman tests to determine the most appropriate estimation method. Results: The findings reveal that NPL and efficiency management (CIR) negatively affect ROA and ROE, showing that credit quality and operational efficiency are key profitability determinants. LLP and CSR positively impact profitability, indicating that prudent risk provisioning and social responsibility initiatives improve financial performance. Digitalization does not significantly impact profitability. Among macroeconomic variables, inflation and currency risk affect ROA, while economic growth influences ROE. Conclusions: This study highlights that internal risk management and operational efficiency remain the primary drivers of bank profitability, while the financial benefits of digitalization may require longer-term implementation and strategic alignment. Limitations: The measurement of digitalization is limited to ATM infrastructure and may not fully capture the broader digital banking innovations. Contributions: This study contributes to the banking literature by integrating digitalization, CSR, and macroeconomic variables into a unified panel data model to explain Indonesian banking profitability.